PENGARUH PENAMBAHAN ABU SEKAM PADI TERHADAP KAPASITAS DUKUNG PONDASI DANGKAL PADA TANAH GAMBUT - Abdurrozak, Muhammad Rifqi (Teknisia, 2018)
Abstract:Various methods of soil improvement have been widely developed, one of the improvement are with soil stabilization as an alternative problem-solving to the subsidence of soil and its bearing capacityy. One of the alternatives given to this model is rice husk ash (RHA) as a filler for stabilization of shallow foundations on peat soils. This paper presents changes in soil bearing capacity and the subsidence that occurs with RHA mixed variations. From the research results obtained that Central Kalimantan peat soil has high organic content of 80,15%. The result of triaxial test with Unconsilidated-Undrained (UU) condition on the original soil obtained cohesion value (c) of 0,645 kg/cm2 and the value of Ï† of 8,6 Â°, while the addition of RHA levels of 8%, during the period of 3 days with cohession value of 0,3089 kg/cm2 and the value of Ï† of 29,53 Â°. The addition of RHA can increase the bearing capacity of the soil to above 100% of the bearing capacity of the original soil. The qult result on the original soil is 750,612 kN/m2, whereas with the addition of RHA, the largest qult value is found at 11% of the seven days duration with the value of 2162,763 kN/m2 and the smallest qult value in the addition of 5% RHA and one day period with a value of 1.010,885 kN/m2.